CUSTOMER ONLINE CUSTOMER RATING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN DI TOKO MODELIAFASHION PADA MARKETPLACE TOKOPEDIA JAKARTA - Luh Kadek Budi Martini; Ejasa Sembiring; Frandy Paulus (Journal of Applied Management and Accounting Science, 2022)
This study aims to determine the Online Customer Rating and Online Customer Review on Purchase Decisions at the ModeliaFashion store on the Tokopedia Marketplace. This research is the result of quantitative research. Sampling using the slovin formula with a total of 60 respondents. Data collection in this study used a questionnaire with a Likert scale. The data analysis method used multiple linear regression analysis. The results of the study show that: (1) Online Customer Rating has a positive and significant effect on purchasing decisions, the t-count value is 1.970 and the significance value is 0.037. (2) Online Customer Review has a positive and significant effect on purchasing decisions, the t-count value is 3.838 and the significance value is 0.000. (3) Online Customer Rating and Online Customer Review have a simultaneous (simultaneous) effect on purchasing decisions, this is evidenced by the f-count value of 56,112 and a significance value of 0.000 and a coefficient of determination of 0.651 which means that purchasing decisions can be explained by Online Customer Rating and Online Customer Review variables are 65.1% while the remaining 34.9% is explained by other variables not included in this study.